Enhancing algal growth and nutrient recovery from anaerobic digestion piggery effluent by an integrated pretreatment strategy of ammonia stripping and flocculation - Qian, Jun; Xu, Chengyu; Song, Hanwu; Zhou, Wenguang; Toda, Tatsuki; Li, Hongwu; Takayama, Yoshiki; Sekine, Mutsumi; Koga, Shinichi; Li, Jun; Liu, Jin (Frontiers in Bioengineering and Biotechnology, 2023)
Anaerobic digestion piggery effluent (ADPE) with quite high ammonium (NH4+) concentration and turbidity (dark brown color) generally needs high dilution before microalgae cultivation, owing to its NH4+ toxicity and color inhibition to algal growth. An integrated pretreatment strategy of ammonia stripping and chemical flocculation may be a more practical pretreatment procedure for enhancing algae yield and nutrient recovery from ADPE. In this study, we determined the optimum pretreatment strategy of ADPE for subsequent microalgae cultivation and nutrient recovery. The results showed that the integrated ADPE pretreatment strategy of high-temperature ammonia stripping, chemical flocculation at the mixed dosage of 2 g L-1 polyaluminum chloride (PAC) and 40 mg L-1 cationic polyacrylamide (C-PAM), and 50 mg L-1 ammonium nitrogen (NH4+-N) enrichment provided maximum algal yield (optical density = 1.8) and nutrient removal (95%, 99%, 99%, and 79% for the removal efficiencies of total nitrogen, NH4+-N, total phosphorus, and chemical oxygen demand, respectively) from ADPE. The integrated pretreatment strategy is expected to become a more practical pretreatment procedure for enhancing algae yield and nutrient recovery from ADPE.